2013
DOI: 10.1111/petr.12150
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features of post‐transplant lymphoproliferative disorders arising after pediatric small bowel transplant

Abstract: Few studies examined the clinicopathologic features of PTLD arising in pediatric SBT patients. Particularly, the association between ATG and PTLD in this population has not been described. Retrospective review of 81 pediatric patient charts with SBT--isolated or in combination with other organs--showed a PTLD incidence of 11%, occurring more frequently in females (median age of four yr) and with clinically advanced disease. Monomorphic PTLD was the most common histological subtype. There was a significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Post-transplant lymphoproliferative disease developed in 18% of patients in our study, which is slightly higher than the reported incidence of about 10%-13% [12][13][14] and may be due to differing immunosuppressive regimens between institutions or the types of transplanted grafts utilized. Similar to others, PTLD in our study occurred more often in pediatric patients, was frequently associated with EBV infection, and most patients had evidence of ACR prior to development of PTLD.…”
Section: Discussioncontrasting
confidence: 73%
“…Post-transplant lymphoproliferative disease developed in 18% of patients in our study, which is slightly higher than the reported incidence of about 10%-13% [12][13][14] and may be due to differing immunosuppressive regimens between institutions or the types of transplanted grafts utilized. Similar to others, PTLD in our study occurred more often in pediatric patients, was frequently associated with EBV infection, and most patients had evidence of ACR prior to development of PTLD.…”
Section: Discussioncontrasting
confidence: 73%
“…However, each of these patients also received sirolimus with standard-exposure CNI, a combination which has been associated with an unacceptably high rate of PTLD in children undergoing kidney transplantation and, indeed, led to premature discontinuation of one study due to PLTD risk [79]. It seems likely that these children undergoing small bowel transplant were over-immunosuppressed, contributing to the high rate of PTLD [77].…”
Section: Retrospective Studiesmentioning
confidence: 96%
“…The limited available retrospective data from liver [78] and lung [76] patients also show no effect of rATG therapy on risk of PTLD. In small bowel transplantation, one series has reported an increased rate of PTLD in a series of children given rATG induction at a cumulative dose of 7.5 mg/kg [77]. rATG in this study was given to the 16 patients who had high titers of de novo donor-specific antibodies (DSA) (n = 11) or to treat rejection (n = 5).…”
Section: Retrospective Studiesmentioning
confidence: 97%
“…The single-center experience published by Nassif et al 6 suggests that the combination of ATG and sirolimus may be linked to more clinically and histologically advanced PTLD. This did not appear to be the case in our experience, possibly because MMF in addition to tacrolimus is our typical maintenance immunosuppression, with sirolimus used for rescue therapy when indicated.…”
Section: Itx Compared With What Has Been Previously Reported In Previousmentioning
confidence: 99%